2011
DOI: 10.1103/physrevlett.106.187601
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Detection of Coherent Nuclear Spin Oscillations in Phosphorus-Doped Silicon using Pulsed ENDOR

Abstract: We demonstrate the electrical detection of pulsed X-band Electron Nuclear Double Resonance (ENDOR) in phosphorus-doped silicon at 5 K. A pulse sequence analogous to Davies ENDOR in conventional electron spin resonance is used to measure the nuclear spin transition frequencies of the 31 P nuclear spins, where the 31 P electron spins are detected electrically via spin-dependent transitions through Si/SiO2 interface states, thus not relying on a polarization of the electron spin system. In addition, the electrica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 25 publications
0
45
1
Order By: Relevance
“…However, whilst the nuclear spin lifetime (T n 1 ) imposes a limit on the storage of classical information, it is the nuclear spin phase coherence time (T n 2 ) which sets a limit on the storage of quantum information, usually shorter than the spin lifetime. Here, we utilize a spin echo technique to show that electrical readout of donor nuclear spins is compatible with phase coherence times T n 2 exceeding 2 ms, nearly two orders of magnitude longer than that previously seen 12 . We also determine that the artificially shortened donor electron lifetime T e 1 limits T n 2 via hyperfine coupling to the nuclei 7 , and discuss ways to overcome this limitation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, whilst the nuclear spin lifetime (T n 1 ) imposes a limit on the storage of classical information, it is the nuclear spin phase coherence time (T n 2 ) which sets a limit on the storage of quantum information, usually shorter than the spin lifetime. Here, we utilize a spin echo technique to show that electrical readout of donor nuclear spins is compatible with phase coherence times T n 2 exceeding 2 ms, nearly two orders of magnitude longer than that previously seen 12 . We also determine that the artificially shortened donor electron lifetime T e 1 limits T n 2 via hyperfine coupling to the nuclei 7 , and discuss ways to overcome this limitation.…”
Section: Introductionmentioning
confidence: 90%
“…For example, coupling the donor electron to the island of a nearby single electron transistor can allow single spin readout 14 , although readout of coherent states of the electron using this technique has not yet been reported in the literature. Hoehne et al 12 have recently shown that electrical readout of coherent nuclear spin motion could be detected using spin dependent recombination, although phase coherence times are limited to T n 2 ∼ 50µs in those measurements. Here, we utilize spin-dependent trapping of photoexcited electrons into the D − state of the 31 P donor 19,20 [ Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The system then evolves freely for a mixing time T, and a stimulated echo is generated by another π/2 pulse. The final π/2 readout pulse is required for electrical detection when the spin-dependent current is governed by spin permutation symmetry rather than spin polarization [4,56,57]. Fig.…”
Section: Appendix D: Eseem Experimentsmentioning
confidence: 99%
“…This scheme allows to extend the experimental methods of pEDMR to more advanced pulse sequences 16,17 and opens its application to other materials and spin-dependent processes to be studied with this technique.…”
mentioning
confidence: 99%